Impact of Primary Cesarean Section on Grand Multiparous Women - Adam Hammad, Kabbashi Mohammed; Suliman, Awadalla Abdelwahid; Ahmed, Hajar Suliman Ibrahim; Omer, Emad Abdalla Siddig; Handady, Siddig Omer M (Clinical Journal of Obstetrics and Gynecology, 2023)
Background: Grand multiparty is common obstetrical problem, in Sudan large families is desirable for cultural and religious backgrounds and higher incidence of grandmultipra is expected, the risk factors associated with adverse maternal outcomes have yet to be adequately investigated among grand multiparity need to delivered by primary cesarean section. Objective: The main objective was to determine impact of primary cesarean section on grand multiparous, it is indications and complications. Methodology: It was a descriptive prospective cross-sectional hospital-based study conducted at Omdurman Maternity Hospital during period October 2016 to March 2017. An interview questionnaire was used for data collection. Demographic and clinical data concerning personal history, parity, indications of primary cesarean section, type of Cs, maternal complication and neonatal complications were recorded. Also, multiparous less than five delivery, previous lower segment caesarean section, known medical disorders except anemia and twin pregnancy were excluded. Results: During the study period total of 113 grand multipara included, incidence of primary cesarean section in grand multipara was 10%. Indication in our study 22.1% due to malpresentation, fetl distress 15% and prolonged first stage 13.4%, prolonged second stage 12.4% and antepartum haemorrhage 11.5%. Postpartum haemorrhage developed in 9.7%, hysterectomy 1.8%, uterine tear 5.4% bladder injury fetal laceration 3.6%, spinal anesthesia headache 7%, post-partum pyrexia 5.3%, sepsis 4.4%, urinary tract infections were 2.7%. Conclusion: The finding in this study showed 10% incidence of primary cesarean section in grandmultipra. The most indications of primary cesarean section in grandmultipra malpresentation, fetal distress, prolonged first and second stage of labour. Most CS were emergency.